Astiotrema turneri n. sp. (Digenea: Plagiorchiidae) from cichlid fishes (Cichlidae: Perciformes) of Lake Malawi, south-eastern Africa - Bray, Rodney A.; van Oosterhout, Cock; Blais, Jonatan; Cable, Joanne (Zootaxa, 2006)
Astiotrema turneri n. sp. is described from the cichlid species Pseudotropheus zebra, P. emmiltos, Labeotropheus trewavasae and Melanochromis vermivorus from Lake Malawi. It differs from Astiotrema reniferum (as described by Yeh & Fotedar 1958) in its distinctly broader body, the much smaller cirrus-sac, its oblique testes, the shorter ventral sucker to ovary distance, the vitellarium reaching into the forebody and the extracaecal uterus; from Astiotrema impletum in the sucker-ratio, the longer caeca, the smaller cirrus-sac and the extracaecal uterus; and from Glossidium pedatum (and its probable synonyms Astiotrema lazeri and Afromacroderoides lazerae) in its much broader body shape, in its distinct oesophagus, the intestinal bifurcation in the posterior forebody, in the distinctly oblique testes, the extracaecal uterus and the vitellarium reaching well into the forebody.